TRIM21 Inhibits the Proliferation and Migration of Lung Adenocarcinoma Cells by Interacting with ZSWIM1 - Luxuan CHEN; Qionghua LIAN; Gui ZHANG; Jiayao WU; Guandi ZENG; Xuejuan GAO (Chinese Journal of Lung Cancer, 2024)
Background and objective Lung adenocarcinoma (LUAD) is a highly morbid and fatal cancer. Despite advancements in modern medical treatment, the 5-year survival rate of patients remains suboptimal. Our previous study revealed that zinc finger SWIM-type containing 1 (ZSWIM1), a novel protein, promotes the proliferation, migration, and invasion of LUAD cells. The aim of this study is to investigate the impact of E3 ubiquitin ligase tripartite motif protein 21 (TRIM21) on ZSWIM1-mediated cell proliferation and migration. Methods The interaction and co-localization between TRIM21 and ZSWIM1 were verified using co-immunoprecipitation (Co-IP) and immunofluorescence (IF). The effects of TRIM21 and ZSWIM1 on the proliferation and migration of LUAD cells were assessed through MTT and Transwell assays, respectively. Western blot (WB) analysis was conducted to evaluate the impact of TRIM21 and ZSWIM1 on the expression of epithelial-mesenchymal transition (EMT) markers in LUAD cells. The influence of TRIM21 on the ubiquitination of ZSWIM1 was examined using Co-IP combined with WB. Results TRIM21 was found to interact and co-localize with ZSWIM1. Overexpression of TRIM21 inhibited the proliferation and migration of LUAD cells. Overexpression of TRIM21 reduced the promoting effect of ZSWIM1 on the proliferation, migration, and invasion of lung adenocarcinoma cells, and reversed the impact of ZSWIM1 on the expression of E-cadherin and Vimentin. Conversely, knockdown of TRIM21 further enhanced the promoting effect of ZSWIM1 on the proliferation and migration of LUAD cells. Mechanistically, we observed that overexpression of TRIM21 significantly enhanced the ubiquitination level of ZSWIM1, leading to a decrease in ZSWIM1 protein expression. Conclusion TRIM21 binds to and promotes the ubiquitination of ZSWIM1, resulting in reduced protein expression of ZSWIM1, which leads to the inhibition of ZSWIM1-mediated promotion of proliferation, migration, and invasion in LUAD cells.